Speech communication in terms of cognition (Revista de Investigaciones Universidad del Quindío, 2022)
The paper presents various approaches to defining the essence of a sign in cognitive science and philosophy of language. It offers presentations of critical review of research publications on sign processes. Based on extensive theoretical work in a cognitive approach to communication process, the hypothesis that each speaker of a language acts exclusively within the framework of their cognitive area is supported in the article. Given the results, meaning as a fact of consciousness is closed in it and during the “translation” of meanings they are not transmitted: signs cannot be considered to be carriers of meanings in the sense that meanings making up a part of their material body are contained in them. The material components of signs stimulate the appearance of identical or similar meanings, actuating analogous conceptual spheres in communicating minds.
Keywords: language sign; communication; cognitive linguistics; biocognitive science; meaning; concept